Healthcare workers preparedness for COVID-19 pandemic in the occupied Palestinian territory: a cross-sectional survey - Osaid Alser; Heba Alghoul; Zahra Alkhateeb; Ayah Hamdan; Loai Albarqouni; Kiran Saini (BMC, 2021)
Abstract Background The COVID-19 pandemic threatens to overwhelm the capacity of a vulnerable healthcare system in the occupied Palestinian territory (oPt). We aimed to evaluate the availability of personal protective equipment (PPE) and the level of preparedness among HCWs in the oPt. Methods A cross-sectional study was conducted using a validated online questionnaire distributed through convenient sampling between March 30, 2020 and April 12, 2020. Outcomes were availability of PPE, healthcare workers (HCWs) preparedness in oPt for COVID-19 pandemic, and regional and hospital differences in oPt in terms of availability of PPE and HCWs preparedness. Descriptive statistics and univariate analysis were used in this study. Results Of 138 respondents, only 38 HCWs (27.5%) always had access to facemasks and 15 (10.9%) always had access to isolation gowns. Most HCWs did not find eye protection (n = 128, 92.8%), N95 respirators (n = 132, 95.7%), and face shields (n = 127, 92%) always available. Compared to HCWs in West Bank, those in the Gaza Strip were significantly less likely to have access to alcohol sanitizers (p = 0.03) and gloves (p < 0.001). On average, governmental hospitals were significantly less likely to have all appropriate PPE than non-governmental institutions (p = 0.001). Only 16 (11.6%) surveyed felt confident in dealing with a potential COVID-19 case, 57 (41.3%) having received any COVID-19-related training, and 57 (41.3%) not having a local hospital protocol. Conclusion HCWs in oPt appear to be underprepared and severely lacking adequate PPE provision. The lack of PPE provision will exacerbate spread of COVID-19 and deepen the crisis, whilst putting HCWs at risk.